Are we aware of radiation: A study about necessity of diagnostic X-ray exposure - Kantarci, Abdulmeci̇t; Koçak, Mehmet; Aydin, Sonay; Ece, Bünyami̇n; Karavaş, Erdal; Esen Bostanci, Işil; Coşgun, Zeli̇ha (Baishideng Publishing Group Inc., 2022)
Total exposure to ionizing radiation has nearly doubled in the last two decades. This increase is primarily due to increased computed tomography (CT) exposure. Concerns have been raised about the risks associated with patients' exposure to medical imaging radiation, which can increase a person's lifetime risk of developing cancer. Preventing unnecessary examinations becomes critical at this point. To avoid unnecessary examinations, it is necessary to understand the demanding process.To ascertain clinicians' awareness of and reasons for requesting a CT examination.We developed an online questionnaire that included 20 questions about clinicians' awareness of radiation safety and their reasons for requesting a CT examination, as well as demographic information such as age, gender, and year of medical practice experience. Additionally, we asked participants the number of CT scans requested in a month, the patients' questions and approaches about the imaging method, the effect of the patient's previous imaging history on the current imaging request, whether they believed that they had sufficient information about radiation doses, and whether they requested CT without an indication. We administered the questionnaire to clinicians from a variety of different professions in four different cities.A total of 195 clinicians participated. Internal medicine specialists were the most crowded group (38/195, 19.5%). Mean age of the population was 33.66 ± 5.92 years. Mean year of experience was 9.01 ± 5.96. Mean number of requested CT scans in a month was 36.88 ± 5.86. Forty-five (23.1%) participants stated that they requested CT scans without clinical indication. The most common reasons for CT scan requests were work load, fear of malpractice, and patient demand/insistence.CT scan requests are influenced by a variety of factors, both internal and external to the doctors and patients. Raising awareness of radiation safety and reducing fear of malpractice by limiting the number of patients per physician may result in a reduction in unnecessary CT examinations and ionizing radiation exposure.
Keywords: Prospective Study; 16. Peace & justice; 3. Good health